2022
DOI: 10.1155/2022/8028275
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Perception of the Impact of Artificial Intelligence in the Decision‐Making Processes of Public Healthcare Professionals

Abstract: Technologies are increasingly independent and play important roles in society. Artificial intelligence (AI) is a branch of science that can improve various environments and processes. The health sector stands out among these contexts, especially ophthalmology and dentistry. Studies evaluating the impact of using these technologies in these contexts are still developing. There are still few studies that assess how AI can impact the decision-making process of health professionals and how it can improve the quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…First, though there is a positive perception of the AI impact on facilitating the decision-making process of certain health professionals (dentists and ophthalmologists) and the quality of patient care in Iraq, a comparable impact has not yet been demonstrated among paediatricians to justify AI application. 7 Therefore, studies on knowledge, attitudes and how AI could influence the decision-making process of paediatricians as well as how it could affect the quality of care provided to sick children are needed. Second, Iraq has faced devastating effects of various crises over the past few decades resulting in disruption of infrastructure.…”
mentioning
confidence: 99%